Chronic social defeat stress caused region-specific oligodendrogenesis impairment in adolescent mice - Chen, Huan; Kang, Zhewei; Liu, Xueqing; Zhao, Yinglin; Fang, Zeman; Zhang, Jinling; Zhang, Handi (Frontiers in Neuroscience, 2023)
Introduction Social stress in adolescents precipitates stress-related emotional disorders. In this study we aimed to investigate oligodendrogenesis in three stress-associated brain regions, medial prefrontal cortex (mPFC), habenula, and amygdala in adolescent mice exposed to social defeat stress. Methods Four-week-old adolescent mice were subjected to social defeat for 10 days, followed by behavioral tests and evaluations of oligodendroglial proliferation and differentiation. Results Stressed mice showed reduced social interaction, more stretched approach posture, lower sucrose preference, but no changes in the forced swimming test. EdU labeled proliferative cells, newly formed NG2+EdU + oligodendrocyte precursor cells (OPCs), and Olig2+EdU+ oligodendrocyte lineage cells (OLLs) were significantly decreased in the mPFC and the lateral habenula, but not in the amygdala and the medial habenula in socially defeated mice. APC+Edu+ newly-generated mature oligodendrocytes (OLs) were decreased in the mPFC in stressed mice. However, the total number of NG2+ OPCs, APC+ mature OLs, and Olig2+ OLLs were comparable in all the brain regions examined between stressed and control mice except for a decrease of APC+ mature OLs in the prelimbic cortex of stressed mice. Conclusion Our findings indicate that adolescent social stress causes emotion-related behavioral changes and region-specific impairment of oligodendrogenesis.